2018
DOI: 10.7567/jjap.57.106402
|View full text |Cite
|
Sign up to set email alerts
|

Performance characterisation of a real-time fiber dosimetry system using radiophotoluminescent glasses

Abstract: We report the first demonstration of a real-time fiber-optic-coupled dosimetry system using Ag-activated phosphate glasses based on radiophotoluminescent (RPL) phenomena. The performance characterisation using real-time fiber RPL glass dosimetry is compared with that of real-time fiber plastic scintillation dosimetry. The inevitable build-up phenomena occurring in Ag-activated RPL glasses both during and after X-ray exposure were measured. The real-time RPL curves for the X-ray exposure region and the build-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…It is not evident to have a dosimetry behavior in this dose range (2 to 222 Gy) using this glass sample. However, the ARGOi* glass sample presents a very strong dynamic for X-ray doses of less than 2 Gy, having a slope sensibility ~1/Gy over 0-2 Gy, which could be of interest to high-sensitivity dosimeter in this range [10].…”
Section: Inscribed Glasses With Silver Clusters For Application To X-...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is not evident to have a dosimetry behavior in this dose range (2 to 222 Gy) using this glass sample. However, the ARGOi* glass sample presents a very strong dynamic for X-ray doses of less than 2 Gy, having a slope sensibility ~1/Gy over 0-2 Gy, which could be of interest to high-sensitivity dosimeter in this range [10].…”
Section: Inscribed Glasses With Silver Clusters For Application To X-...mentioning
confidence: 99%
“…As RPL is known to be an established method for the determination of the absorbed doses [3,[5][6][7], this technique can be applied to the individual monitoring of ionizing radiation as well as the monitoring of the natural environmental and/or manmade-emitting radiations in the dose range from tens of µGy up to several hundreds of Gy [9]. To better characterize the environmental radiation, RPL glasses have been coupled to a fiber system to obtain real-time dosimetry technology by continuously exciting the glass and collecting its RPL signal [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has already been reported that the main factors affecting the rate of build-up are the temperature, chemical composition of the glass, and Ag concentration. (31)(32)(33)(34)(35)(36) However, the reason why the rate of build-up depends on the Ag concentration has not yet been investigated. The Ag-doped PANS glass samples were synthesized by the following method.…”
Section: Introductionmentioning
confidence: 99%
“…RPLDs have been researched for application for in vivo brachytherapy [213], personal monitoring and clinical dosimetry by Chiyoda Technol Corporation in Japan [214] and real-time fibre-optic-coupled dosimetry system [215]. Silver (Ag) activated phosphate glass is the most widely used RPLD material [215].…”
Section: Radiation Dosimeters and Materialsmentioning
confidence: 99%
“…RPLDs have been researched for application for in vivo brachytherapy [213], personal monitoring and clinical dosimetry by Chiyoda Technol Corporation in Japan [214] and real-time fibre-optic-coupled dosimetry system [215]. Silver (Ag) activated phosphate glass is the most widely used RPLD material [215]. Ag-doped phosphate glasses constitute different luminescent centres, where irradiation generates charge carriers and electron or hole trapping at Ag + .…”
Section: Radiation Dosimeters and Materialsmentioning
confidence: 99%